2018
DOI: 10.1089/ten.tea.2017.0285
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Extracellular Matrix Protein Fragments Support Human Embryonic Stem Cell Chondrogenesis

Abstract: We previously developed a 14-day culture protocol under potentially GMP, chemically defined conditions, to generate chondroprogenitors from human embryonic stem cells (hESCs). In vivo work has confirmed the cartilage repair capacity of these cells in a nude rat osteochondral defect model. Aiming to enhance hESC-chondrogenesis, we screened a range of extracellular matrix (ECM) molecules for their ability to support differentiation of hESCs toward chondrocytes. We identified two novel ECM protein fragments that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…This is because of the ECM properties of Matrigel, which can promote the osteogenic differentiation of BMSCs directly. The ECM has already been reported to provide structural support for cells and physical and biochemical cues to regulate cell phenotype [ 23 , 24 ]. BMSCs cultured in Matrigel can interact with multiple ECM components within the Matrigel, such as laminin and TGF- β .…”
Section: Discussionmentioning
confidence: 99%
“…This is because of the ECM properties of Matrigel, which can promote the osteogenic differentiation of BMSCs directly. The ECM has already been reported to provide structural support for cells and physical and biochemical cues to regulate cell phenotype [ 23 , 24 ]. BMSCs cultured in Matrigel can interact with multiple ECM components within the Matrigel, such as laminin and TGF- β .…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant human (rh) laminin-511 [35], rh vitronectin [36], and rh E-cadherin [37] were considered as the noteworthy landmarks when at the first time they were applied in the culture of hPSCs as the xenogeneic-free substrates. In addition, the recombinant protein fragments recombinant fibronectin fragment (FN III) and FBNI fragment (PF8) supported the human embryonic stem cell chondrogenesis [38]. Furthermore, the mixtures of fibronectin, Figure 2: Gelatin endorses the iPSCs to differentiate into consequent several phased neural cells.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have demonstrated that hydrophilic surfaces enhance chondrogenic phenotypes by limiting protein adsorption and cell spreading, promoting a more spherical morphology [ 51 , 55 , 56 ]. Such a spherical phenotype is correlated with synthesis of a chondrogenic matrix [ 57 , 58 , 59 ]. Contact angle measurements revealed PEU to be significantly more hydrophilic than PCL and confocal microscopy images suggest that seeded cells exhibit reduced spreading on PEU scaffolds.…”
Section: Resultsmentioning
confidence: 99%